Germline Testing for Patients With BRCA1/2 Mutations on Somatic Tumor Testing. Issue 1 (11th November 2019) - Vlessis, Katherine; Purington, Natasha; Chun, Nicolette; Haraldsdottir, Sigurdis; Ford, James M
Abstract: Background: The National Comprehensive Cancer Network (NCCN) recommends germline testing for pathogenic BRCA1/2 mutations identified by somatic tumor sequencing. The aim of this study was to explore whether patients at Stanford with somatic BRCA1/2 mutations were recommended germline testing in accordance with NCCN guidelines. Methods: We retrospectively collected all Stanford patients with BRCA1/2 mutations found by tumor sequencing. Medical records were reviewed for each patient to identify those recommended germline testing. A multivariable logistic regression model was fit associating baseline characteristics with whether or not a recommendation was made. Results: Of 164 participants, 51 (31.1%) had no recommendation for germline testing. Of the 97 available germline-testing results, 54 (55.7%) were positive for pathogenic BRCA1/2 mutations. After adjusting for possible confounders, patients with genitourinary cancer (odds ratio [OR] = 0.03, 95% confidence interval [CI] = 0.00 to 0.03; P  =   .003), lung cancer (OR = 0.04, 95% CI = 0.01 to 0.21; P  <   .001), sarcoma (OR = 0.02, 95% CI = 0.00 to 0.14; P  <   .001), skin cancer (OR = 0.01, 95% CI = 0.98 to 1.03; P  =   .002), or "other" diagnoses (OR = 0.01, 95% CI = 0.00 to 0.16; P  <   .001) were statistically significantly less likely to be recommended germline testing compared with patients with breast or gynecological cancers. Conclusions: Our study highlights the importance of provider education outside of the oncologic specialties typically associated with BRCA -related cancers and continued exploration of referrals to genetics for germline testing on the basis of somatic findings.